Internet and Social Media Habits Among Basrah University Students - Wahab, Saba Adnan Abdul; Abdullah, Zinah Abdulsttar; Shraida, Ghofran Khaled; Shihab, Luay Abdulwahid; Khudhiar, Abdulkareem Salman; Awwad, Zamzam; Hameed, Eman Saeed; Hussein, Zahraa Abdul (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Social media is an internet communication medium that has become essential to our daily lives. It makes it possible for individuals to create web content, communicate, and share data. The purpose of this essay is to illustrate how social media affects a sample of Iraqi university students' academic achievement, social interactions, and mental health. Patients and methods: A questionnaire was used to gather data from 430 Iraqi students from various colleges who participated in the study. Results: The cell phone was the most popular device (95.9%) for social media viewing, and the majority of the sample (98.4%) reported using social media currently. According to the study, social media can affect academic achievement and social interaction in both positive and negative ways. The majority of participants (60.7%) and (21.6%) agreed and strongly agreed that social media use is enhancing interpersonal connections and information sharing. Nonetheless, 30.9% of respondents strongly agreed that social media might cause them to spend less time with friends and family. In terms of academic performance, the majority of the sample (44.5%) strongly agreed that using social media could cause them to waste time that could be spent studying, and 26.8% strongly agreed that it diverted their attention. Among those pupils, over half (53.4%) agreed and strongly agreed that social media negatively impacts their overall academic performance. Conclusion: The study found that university students' academic performance, social interactions, and mental health are all significantly impacted by social media, and that raising awareness among them is crucial to reducing excessive and harmful usage of the platform. Highlights: Academic Distraction: 53.4% say social media hurts their studies. Mixed Social Impact: Boosts communication but cuts family time. Need for Awareness: Students must manage usage to protect well-being. Keywords: University Students, Academic Performance, Mental Health, Social Relationships , Social Media